Answer:
see explanation
Step-by-step explanation:
Given
(x - 3) × (x + 4) = 0, that is
(x - 3)(x + 4) = 0
The zero product indicates that (x - 3) = 0 or (x + 4) = 0
x - 3 = 0 ⇒ x = 3
x + 4 = 0 ⇒ x = - 4
Thus if x = 3, then
(3 - 3)(x + 4) = 0 × (x + 4) = 0
Similarly if x = - 4 the output is zero
Answer:
20
Step-by-step explanation:
<u>25 </u> = <u> x</u>
20 16
(25*16)/20 = 20
✧・゚: *✧・゚:* *:・゚✧*:・゚✧
Hello!
✧・゚: *✧・゚:* *:・゚✧*:・゚✧
❖ The least common denominator of 3/4 4/5 and 2/3 is 60.
4 x 15 is 60, 5 x 12 is 60 and 3 x 20 is 60.
~ ʜᴏᴘᴇ ᴛʜɪꜱ ʜᴇʟᴘꜱ! :) ♡
~ ᴄʟᴏᴜᴛᴀɴꜱᴡᴇʀꜱ
Answer:
I'm not sure about "11" but 12. is "by the definition of right angles", and 16. is "by the SAS(side angle side) congruency theorem"